ENGAGING STUDENTS’ WRITING SKILL BY USING PICTURE CUED TASK - Ananda Oktaviani, Fadilah; Nuraini, Hery; Mulyana, Agus (JIPIS, 2025)
The aim of this research was to know whether there is a significant effect of teaching by using picture cued task toward students’ writing skill at the tenth grade of SMAN 14 Kota Tangerang. The method of the research used quantitative research and for the design of the research is Quasi- Experimental research with one group by using pre-test and post-test in experimental class. Students test was used by the writer to collect the data through pre-test and post-test. The result of this research was statistical calculation by One-Sample Kolmogorov-Smirnov test, it is known the asymptotic significances of the pre-test and post-test in experimental class data is 0.000 (0.05). it can be concluded that there is positive effect of the use picture cued task in engaging students writing skill.